2001
DOI: 10.1175/1520-0485(2001)031<3030:tropsb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Rhine Outflow Plume Studied by the Analysis of Synthetic Aperture Radar Data and Numerical Simulations

Abstract: The dynamics of the Rhine outflow plume in the proximity of the river mouth is investigated by using remote sensing data and numerical simulations. The remote sensing data consist of 41 synthetic aperture radar (SAR) images acquired by the First and Second European Remote Sensing satellites ERS-1 and ERS-2 over the outflow region of the river Rhine. Most of them show sea surface signatures of oceanic phenomena, for example, surface current and wind variations, ship wakes, and oil slicks. In particular, in 36 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…In some cases, there are as many as 10 undulation cycles. Similar SAR backscatter patterns have been identified to be internal waves using theory and in situ data at other locations [ Hessner et al , 2001]. J. D. Nash and J. N. Moum (River plumes as a source of large amplitude internal waves in the ocean, submitted to Nature , 2005) present detailed observations of internal waves or solitons generated at Columbia plume fronts.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In some cases, there are as many as 10 undulation cycles. Similar SAR backscatter patterns have been identified to be internal waves using theory and in situ data at other locations [ Hessner et al , 2001]. J. D. Nash and J. N. Moum (River plumes as a source of large amplitude internal waves in the ocean, submitted to Nature , 2005) present detailed observations of internal waves or solitons generated at Columbia plume fronts.…”
Section: Resultsmentioning
confidence: 57%
“…We estimate the local front velocity and direction from repeated measurements of front location from two vessels and a helicopter, then verify that these estimates are reasonable using synthetic aperture radar (SAR) images for similar ocean, tide and wind conditions. Banded regions of elevated SAR backscatter are generally found in association with strongly convergent river plume fronts (Figure 1a), due to modulation of sea surface roughness caused by the convergence at the leading edge of the front and divergence after its passage [ Hessner et al , 2001].…”
Section: Measurements and Analysesmentioning
confidence: 99%
“…In this paper we investigate aspects of the hydrodynamics of the Ross Sea related to the spreading and sinking of the DISW in two ways. First, by means of in situ observations and then by the results of a nonlinear, reduced gravity, frontal layered numerical model which is able to simulate the dynamics of isolated ("frontal") water masses and hence the dynamics of a bottom trapped current over realistic topography (Hessner et al 2001, Rubino et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Kilcher and Nash [1] gave a comprehensive review on "tidal plume fronts" (in their terminology) which are formed by ebb discharge from a river's mouth. Visual observations [2], instrumental observations [1,3,4], marine radar observations at grazing angle (e.g., [1,5,6]), and radar observations from space (e.g., [7,8]) are the major means of detecting and following river plume fronts with the main purposes of elucidating the spatial and temporal behavior of the fronts, mixing processes, flow structures of river and sea water, and propagation dynamics. Garvine and Monk [2] made field observations of vertical distributions of current velocity, water temperature, and salinity at the mouth of the Connecticut River, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Images of synthetic aperture radar (SAR) have been analyzed to understand the behavior of outflows of large rivers. Hessner et al [7] analyzed the behavior of river plume fronts observed along the Rhine River outflow into the North Sea by European radar satellites ERS-1 and ERS-2. They assert that the formation and the locations of the frontal features are mainly linked to the semidiurnal tidal phase in the outflow region.…”
Section: Introductionmentioning
confidence: 99%